PERDAGANGAN ONLINE KURA-KURA DAN BULUS (REPTILIA: TESTUDINES) DI DAERAH ISTIMEWA YOGYAKARTA - Lathifatul Faliha; Christian Manggala Yudha Pratama; Ainun Ni’matil Fitriyah; Rury Eprilurrahman (Scripta Biologica, 2019)
The Asian freshwater tortoise and fresh water turtle population is currently under threat from various types of human behavior (Van Dijk et al., 2000). In Indonesia, the turtle trade is increasingly prevalent because of the increase in turtle lovers in various regions and there are still people who consume turtles (soft shelled turtle). This study aims to find out the species and size variations of members Order Testudines traded in the Daerah Istimewa Yogyakarta. The method used in this study is online survey in social media such as Facebook, OLX Website, and Instagram to seller and reptile lovers (are traders too). The survey results in the online survey were 35 species from 9 families, which consists of 32 species (7 families) including turtle groups, and 3 species (2 families) including Soft Shelled Turtle. Two species is protected in Indonesia that is Orlitia borneensis and Carettochelys insculpta, then two species protect in Appendices I CITES that is Astrochelys radiata and Geochlemys hamiltonii, and the size variation the most common individuals are juvenile to adult individuals.